The Impact of Educational Attainment and Professional on Women's Income Contribution in Indonesian Human Resource Management - AZALIA, ARETA NUR FATIMAH (Benefit: Jurnal Manajemen dan Bisnis, 2024)
This study analyzes the influence of women professional workers and women's education levels on women's income contributions. The data used are secondary data obtained from the Central Statistics Agency (BPS), using data at the provincial level for 2018-2022. The method used in this study is panel data regression. This study found that the variable of women professional workers positively affects women's income contributions. In addition, the results show that the variable of women's education level positively affects the variable of women's income contributions, especially elementary and high school education levels.